Blood lead levels in low-income and middle-income countries: a systematic review. Issue 3 (March 2021) - Ericson, Bret; Hu, Howard; Nash, Emily; Ferraro, Greg; Sinitsky, Julia; Taylor, Mark Patrick
Summary: Background: Since the global phase-out of leaded petrol, reports have suggested that lead exposure remains substantial or is increasing in some low-income and middle-income countries (LMICs). However, few studies have attempted to systematically assess blood lead levels over the full range of LMICs. We aimed to describe values for blood lead level in LMICs. Methods: In this systematic review, we searched PubMed for studies published between Jan 1, 2010, and Oct 31, 2019, that reported blood lead levels in the 137 countries in World Bank LMIC groupings. Studies were reviewed for inclusion if they contained blood lead level data from human populations residing in any given country; comprised at least 30 participants; presented blood lead level data derived from venous, capillary, or umbilical cord samples of whole blood; had data that were collected after Dec 31, 2004; and were published in English. Data on blood lead level were extracted and pooled, as appropriate, to make country-specific estimates of the distribution of background blood lead levels among children and adults, along with information on specific sources of exposure where available. This study is registered with PROSPERO, number CRD42018108706. Findings: Our search yielded 12 695 studies, of which 520 were eligible for inclusion (1100 sampled populations from 49 countries comprising 1 003 455 individuals). Pooled mean blood lead concentrations in children ranged from 1·66 μg/dL (SD 3·31) in Ethiopia to 9·30 μg/dL (11·73) in Palestine, and in adults from 0·39 μg/dL (1·25) in Sudan to 11·36 μg/dL (5·20) in Pakistan. Background values for blood lead level in children could be pooled in 34 countries and were used to estimate background distributions for 1·30 billion of them. 632 million children (95% CI 394 million–780 million; 48·5%) were estimated to have a blood lead level exceeding the US Centers for Disease Control's reference value of 5 μg/dL. Major sources of lead exposure were informal lead acid battery recycling and manufacture, metal mining and processing, electronic waste, and the use of lead as a food adulterant, primarily in spices. Interpretation: Many children have a blood lead level exceeding 5 μg/dL in LMICs, despite leaded petrol phase-outs. Given the toxicity of lead, even at low amounts of exposure, urgent attention is required to control exposures and to expand population-based sampling in countries with no or scant data. Funding: This work was supported by the United States Agency for International Development (Cooperative Agreement number AID-OAA-A-16-00019).